Spectrophotometric Assay of Lead in Human Hair Samples by using alizarin red (S) in Samarra area - Khalaf Faris Alsamarrai (مجلة جامعة الانبار للعلوم الصرفة, 2012)
A new spectrophotometric method for determination of lead in human hair samples was developed. The method is based on the reaction of lead(II) with alizarin red(S) in basic medium to form a pink red water soluble complex which gave a maximum absorbance at 518 nm. The optimum conditions (effect of Nitric acid and hydrogen peroxide pH of medium, time effect, heating effect and reagent concentration) were investigated. The method obeyed to beer’s law over the concentrations range 1.50 ppm -9.00 ppm with molar absorptivity = 32522.96 l.mol-1.cm-1 and Sandell index 0.0064μg.cm-2. It was applied successfully to determination of lead in pure and human hair samples with high sensitivity and good validity.